The Effect of Service Quality And Price on Customer Satisfaction in Po. Sumber Alam - Andi Supiandi (Peneliti.net, 2022)
This study aims to determine the effect of service quality and price variables, either simultaneously or partially, on customer satisfaction at the Sumber Alam Autobus Company, especially the night bus majoring in Yogyakarta – Jakarta. In addition, the purpose of this study was to determine the level of customer satisfaction based on these independent variables. The data collection technique was done by using a questionnaire method to 100 respondents. Methods of data analysis using multiple linear regression analysis using SPSS 17.0 for Windows. The conclusion from the results of this study indicate that the variables of service quality (X1) and price (X2) have a positive and significant effect on customer satisfaction at PO. Sumber Alam Yogyakarta-Jakarta Department, either simultaneously or partially. Simultaneous test results show the calculated F value of 59.885 is greater than F table which is 3.098. The calculated t-value for the service quality variable is 5.900 and the price variable is 4.561, which is greater than the t-table value which is only 1.985. Based on the value of the coefficient of determination (Adjusted R2) shows a value of 0.543, meaning that 54.3% of customer satisfaction is influenced by service quality and price, while the remaining 45.7% is influenced by other variables.